Analisis Isi Pesan Dakwah dalam Akun @Nugarislucu pada Media Sosial Twitter dengan Studi Kasus Tanggal 01 Maret 2020 - 01 April 2020 - Risma Eko Prastiyo; Luthfi Hidayah (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2020)
The background of this research is the @NUgarislucu account which has a unique characteristic where the account preaches in a different way, each da'wah has its own message and it is packed with humor or jokes. The platform used is social media Twitter which is now busy being used, especially by millennials. The research entitled